Automatic Leviathan: Cybernetics and politics in Carl Schmitt's postwar writings. (February 2020) - Guilhot, Nicolas
This article questions the current vogue of Carl Schmitt among political theorists who read him as an antidote to the depoliticizing force of economics and technology in the age of neoliberalism and its algorithmic rationalities. It takes Schmitt's sparse reflections about cybernetics and game theory as paradigmatic of the theoretical and political problems raised by any theory positing the autonomy of the political. It suggests that this ultimately misunderstands the role of cybernetic representations of political decision-making in shoring up in the 1960s and 1970s the autonomy of the political that Schmitt so vehemently defended.